Locally Injectable Chitosan/β-Glycerophosphate Hydrogel Doped with Triptolide-Human Serum Albumin Nanoparticles for Treating Rheumatoid Arthritis - Pu Yao; Zirui Tan; Bangbi Weng; Xiaowen Wang; Hongping Wang; Ge Yang; Fengjun Sun; Ying Zhao (MDPI AG, 2024)
Background: Rheumatoid arthritis (RA) tends to occur in symmetrical joints and is always accompanied by synovial hyperplasia and cartilage damage. Triptolide (TP), an extract from Tripterygium, has anti-inflammatory and immunomodulatory properties and could be used in the treatment of RA. However, its poor water solubility and the multi-system lesions caused by the use of this substance limit its clinical application. Therefore, it would be of great significance to assemble a composite nanoparticle hydrogel and apply it to a collagen-induced arthritis (CIA) mouse model to investigate the therapeutic effect and biosafety of this compound. Method: TP@HSA nanoparticles (TP@HSA NPs) were fabricated with a self-assembly method; a thermosensitive hydrogel loaded with the TP@HSA NPs (TP@HSA NP hydrogel) was prepared by using chitosan and beta- glycerophosphate (β-GP) and was then intra-articularly injected into CIA mice. The changes in joint swelling were measured with a digital caliper, and inflammation and cartilage damage were evaluated by using hematoxylin and eosin (H&E) and safranin O-fast green (SO&FG) staining, respectively. Results: TP@HSA NPs with an average diameter of 112 ± 2 nm were successfully assembled, and their encapsulation efficiency and drug loading efficiency were 47.6 ± 1.5% and 10.6 ± 3.3%, respectively. The TP@HSA NP hydrogel had a gelation temperature of 30.5 ± 0.2 °C, which allows for its injection at low temperatures and its sol-gel transformation under physiological conditions within 2 min, making it a suitable drug depot. The TP@HSA NP hydrogel was intra-articularly injected into CIA mice; it released TP locally and exerted anti-inflammatory and immunomodulatory effects, alleviating synovial inflammation and cartilage damage effectively. Conclusions: We successfully fabricated a TP@HSA NP-loaded thermosensitive hydrogel with good biosafety, which can release TP slowly for the treatment of RA. Our study provides a basis for the development of TP-based innovative preparations and has good application prospects.